Virtual machine placement in distributed cloud centres using bin packing algorithm. (2018) - Kumaraswamy, S.; Nair, Mydhili K.
Virtual machine is a logical framework to provide services on the cloud. These virtual machines form a logical partition of the physical infrastructure present in the cloud centre. Virtual machines are not only prone to cost escalation but they also result in huge power consumption. Hence, the cloud centre needs to optimise cost and power consumption by placing these virtual machines from their current physical machines to other suitable physical machines. Currently, this problem has been addressed by considering the virtual machines present in a single location cloud centre. But, currently cloud centres have multiple locations and all of them are synchronised to provide cloud services. In this complex paradigm, it is important to differentiate the same and different location virtual machines and provide suitable placement algorithms. In this work, the problem of virtual machine placement is modelled through the three slot bin packing problem. It is shown as NP-complete and suitable approximation algorithms are proposed. Also, polynomial time approximation scheme is designed for this problem which provides a facility to control the quality of approximation. Empirical studies performed through simulation confirm the theoretical bounds that were obtained.